Learning more from feedback: Elaborating feedback with examples enhances concept learning. (April 2018) - Finn, Bridgid; Thomas, Ruthann; Rawson, Katherine A.
Abstract: Two experiments investigated whether elaborating practice-test feedback with conceptual examples could increase conceptual understanding. In the present study, participants studied psychology terms and definitions. During the practice test phase, the definition was presented and participants attempted to recall the corresponding concept term. Immediately after responding, half of the participants were given feedback that provided the correct term. The other half was shown the correct term, followed by presentation of a concept example. To assess concept learning, in Experiment 1 participants were given a final cued recall test in which they were presented with either the previously studied definition or a new example and were prompted to provide the correct concept term. The results of Experiment 1 showed that elaborated feedback enhanced performance on tests of both the definitions and the new examples. In Experiment 2 participants took final classification tests to rule out the possibility that feedback elaborated with examples primarily facilitated access to the term name rather than strengthening conceptual understanding. Results demonstrated that presentation of examples during feedback bolstered performance across all test types and formats. Highlights: Presentation of examples along with conceptual definitions can strengthen conceptual learning. Feedback during a test offers another learning opportunity. The effects of feedback can be amplified by more elaborate processing of the feedback. Two experiments investigated whether elaborating feedback with conceptual examples could increase conceptual understanding. Feedback elaborated with examples benefitted tests of definitions and new examples on classification and cued recall tests.